M-Learning in ELT: Avenues and Challenges that Confront Teaching and Learning at Higher Education - Yuliani, Sri; Kaur, Naginder; Singh, Amreet Kaur Jageer (International Journal of Language Education, 2023)
Technology can be directed to provide effective and productive pedagogy in the English language classroom. One of these fairly recent technological platforms for English language teaching and learning is the mobile phone. Also known as m-learning, it offers valuable opportunities for educators to create effective teaching strategies through the utilisation of mobile phones. On the receiving end of this pedagogical strategy are our students, our clients, whose perspectives and attitudes towards m-learning warrant equaly important considerations. Thus, this study was pursued to probe the role of mobile phone for English language learning in the Indonesian context. The study was guided by the theory of connectivism, activity theory, and communities of practice. This case study adopted a mix of qualitative and quantitative means for the purpose of accumulating data with semi-structured interviews and questionnaires as primary research instruments. It was learnt through the study that students are generally in favour of and have positive responses on the use of mobile phones in language learning but several emergent problems need to be addressed by institutional administrators and classroom instructors when tapping on m-learning. These research findings pave the way for subsequent research endeavours to delve into the efficacy of m-learning as a viable mediating variable for language learning, especially in the wake of prevalent online learning scenario, where mobile phones have become an integral part of online and distance learning platforms.